ANALISIS PENERAPAN HARGA PASAR BERDASARKAN TINGKAT PRODUKSI PADA KOMODITAS CABAI MERAH DALAM PERSPEKTIF MAQASHID SYARIAH (Studi Kasus: Kelompok “Juli Tani” Desa Sidodadi Ramunia, Kecamatan Beringin, Kabupaten Deli Serdang, Sumatera Utara) - Ellina Satyana; Muhammad Arif; Nuri Aslami (J-EBI: Jurnal Ekonomi Bisnis Islam, 2023)
ABSTRACTThis study aims to analyze the application of market prices based on production levels on red chili from the maqashid sharia perspective by the Juli Farmers Group in Sidodadi Ramunia Village, Beringin District, Deli Serdang Regency, North Sumatra. This research is a descriptive qualitative research, the data collection methods are observation, interviews and documentation. The subject of this study was focused on 30 red chili farmers using a purposive sampling technique. The results of this study indicate that changes in the price of red chilies on the market do not affect the high or low quantity of red chili production produced by farmer Juli Tani, Sidodadi Ramunia Village. Fluctuations in chili prices have not made red chili farmer Juli Tani switch to producing other commodities. The most basic reason for this decision is due to a strong belief in interest and experience in red chili farming, as well as other factors that affect production such as land area, labor and fertilizer. The average net income of Juli Tani's red chili farmers with 1,050 kg/rante in one harvest is Rp. 5,682,500, whereas if calculated per year Rp. 11,065,000 or around Rp. 1,844,166/month. The application of maqashid sharia in looking at market prices is when at-tas'ir (pricing) is permitted if human benefit can be realized. Islam requires the government to intervene in prices if there are indications of market distortions. For the application of maqashid sharia, the level of production is assessed from the Maslahah (M) value obtained by the Juli Red Chili Farmers Group, Sidodadi Ramunia Village in production activities, namely Rp. 11,715,000. Keywords: Market Prices, Production Levels, Commodity Red Chili, Maqashid Syariah